Global public good and universal health coverage: conceptual and practical concerns in the context of COVID-19 - Nayar, Rajasekharan K. (International Journal Of Community Medicine And Public Health, 2021)
The notion of public good has been reclaimed in recent times due to the pandemic as in many countries including the United States, the existing infrastructural, strategic and investment limitations have been realized. There is need for a debate on the notion of global public good especially with respect to health and to bring out the incommensurability of the notion. Along with these realizations and reclamations, issues related to the three A’s- accessibility, availability and affordability of health car have also been raised as a part of universal health coverage (UHC). The three A’s have become more relevant in the context of the pandemic. However, the ideological underpinnings of such conceptual reclamations and probable linkages need to be discussed. In fact, public good assumes the distribution of services equally to all members of the society which is problematic as it may not take care of equity issues in societies where some people suffer more and need special care and services. Public good is a ‘troubled’ notion which has its origin and also has been used in neo-classical and neoliberal approaches and it cannot be recommended without a proper understanding of the diverse ways in which the concept has been treated. The need for current claiming or reclaiming of such concepts started with environmental goods (although not many the so-called environmentalists realise it) to highlight destruction of global commons or resources which will result in loss of markets and therefore profits. The present reclaiming of the concept is also because of such a realisation as the pandemic has affected market interests. New approaches are evolving because of the so-called ’aid fatigue’ of donors as they think that economic aids may be irrelevant at this time as the rich countries are also suffering and therefore, let them manage on their own!